Aplikasi Virtual Kata Untuk Komunikasi Penyandang Tunarungu Berbasis Android - Fras Setia Rahman; Yuhefizar Yuhefizar (Ikatan Ahli Informatika Indonesia (IAII), 2017)
Deaf people are people who lose either their partial or complete hearing ability which will make the sense of hearing unusable. The problem encountered when meeting a deaf person is unable to communicate well. To solve this problem, it is necessary to build a virtual word application that is android based to help communicate with the deaf people. This app uses 3D virtual characters as a voice-translating medium into a sign language. The sign language is converted to 3D animation to make it easier to understand and attractive. The sign language system used in this application is the SIBI system (Sistem Isyarat Bahasa Indonesia). This application is built by using Unity 3D software with C # and Java programming language, while to create 3D animation is using Blender software. From the test results of this application, obviously it can facilitate the communication with the deaf people. Keywords: word virtual application, deaf communication, 3D sign language animation, SIBI, android.